A recurrent retrohepatic abscess secondary to a dropped appendicolith - Shahzeb Sheikh, BSc (Hons), MBChB; Muskan Kaur, BMedSci; Abed M. Zaitoun, PhD, FRCPath; Dileep N. Lobo, DM, FRCS, FACS, FRCPE (Radiology Case Reports, 2024)
Appendicoliths can drop into the peritoneal cavity during the course of an appendicectomy, or more commonly as a result of perforated appendicitis. We report the case of a patient with a history of recurrent retrohepatic abscesses over 7-year period due to a retained appendicolith and review the literature on perihepatic abscesses caused by retained appendicoliths. The abscess had been drained percutaneously 4 times without retrieval of the appendicolith and eventually the patient needed a laparotomy, drainage of the abscess, and extraction of the appendicolith. Treatment of abscesses secondary to dropped appendicoliths may be percutaneous, laparoscopic, or via conventional open surgery, but it is important to retrieve the appendicolith if recurrent abscess formation is to be avoided.